PENERAPAN MEDIA PEMBELAJARAN KOTAK DAN KARTU MISTERIUS (KOKAMI) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 12 PEKANBARU - Nia Audina; Rini '; Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research was conducted because of the low learning achievement of student on the structure of atom and the periodic system of element who has not reached the minimum completeness criteria (KKM) was 75 that have been established in school. The research aimed to improve the achievement of learners on structure of atom and the periodic system of element subject in X class SMAN 12 Pekanbaru. This research was a kind of experimental research with pretest-posttest design. The research was conducted in SMAN 12 Pekanbaru the samples of the research were the students of X MIPA1 class as the experimental class and students of X class MIPA4 as the control class which were determined randomly after doing normality test and the homogeneity test. The learning process of experimental class and control class used scientific approach which was based on the curriculum in 2013. Experimental class was a class which was given the treatment that used mysterious box and cards media while the control class was not. The data analysis technique we used was the t-test, criteria testing H0 accepted if tcount ttabel dk = n1 + n2 – 2 with α = 0,05. Based on the result of data analysis test, we obtained tcount ttabel was 3,81 1,67. It meant that the use of mysterious box and cards media could improve students learning achievement on structure of atom and the periodic system of element subject in X class SMAN 12 Pekanbaru.Key Words : Mysterious Box and Cards Media, Learning Achievement, Structure of Atomand The Periodic System of Element